John William Draper family papers - Draper, John William, 1811-1882.; Draper, Daniel, 1841-1931.; Draper, Henry, 1837-1882.; Draper, John C. (John Christopher), 1835-1885.
Correspondence; manuscript and printed copies of speeches, articles, and books; subject files; financial records; family papers; and other papers relating to Draper's career as a scientist and historian. Documents his work as president of the New York University Medical Dept. (1850-1882), nomination as president of the American Chemical Society, address (1860) before the British Association for the Advancement of Science, and writings including the Life of Franklin (unpublished until 1977) and History of the American Civil War (1867-1870). Subjects include the exchange between Samuel Wilberforce and Thomas Huxley on Darwin's theory on the origin of species.
Correspondents include Alexander Agassiz, Benjamin Alvord, Theodorus Bailey, George Bancroft, F.A.P. Barnard, George Bell, Schuyler Colfax, George W. Cullum, John Adolphus B. Dahlgren, James Dwight Dana, William Darling, Charles Darwin, John Gibbon, W.E. Gladstone, Ulysses S. Grant, William Babcock Hazen, John F.W. Herschel, Oliver Wendell Holmes, Benson John Lossing, Valentine Mott, Simon Newcomb, William T. Sherman, Benjamin Silliman, Herbert Spencer, Ainsworth Rand Spofford, Edwin McMasters Stanton, John Tyndall, Gideon Welles, J.D. Whitney, Thomas John Wood, and William Jay Youmans.
Also includes papers of Draper's sons, John C. Draper, Henry Draper, and Daniel Draper; and other members of the Draper, Maury (Morey), and Ludlow families. Papers of Daniel Draper relate to his work (1869-1911) with the New York Meteorological Observatory and include correspondence with Cleveland Abbe, Alexander Graham Bell, James McKeen Cattell, Gustave Eiffel, Valentine Mott, C. Piazzi Smyth, and John Tyndall.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Scientist and historian.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abbe, Cleveland, -- 1838-1916 -- Correspondence; Agassiz, Alexander, -- 1835-1910 -- Correspondence; Alvord, Benjamin, -- 1813-1884 -- Correspondence; Bailey, Theodorus, -- 1805-1877 -- Correspondence; Bancroft, George, -- 1800-1891 -- Correspondence; Barnard, F. A. P. -- 1809-1889 -- Correspondence; Bell, Alexander Graham, -- 1847-1922 -- Correspondence; Bell, George, -- 1814-1890 -- Correspondence; Cattell, James McKeen, -- 1860-1944 -- Correspondence; Colfax, Schuyler, -- 1823-1885 -- Correspondence; Cullum, George W. -- 1809-1892 -- Correspondence; Dahlgren, John Adolphus Bernard, -- 1809-1870 -- Correspondence; Dana, Edward Salisbury, -- 1849-1935 -- Correspondence; Dana, James Dwight, -- 1813-1895 -- Correspondence; Darwin, Charles, -- 1809-1882.; Darwin, Charles, -- 1809-1882 -- Correspondence; Darling, William, -- 1802-1884 -- Correspondence; Eiffel, Gustave, -- 1832-1923 -- Correspondence; Franklin, Benjamin, -- 1706-1790.; Gibbon, John, -- 1827-1896 -- Correspondence; Gladstone, W. E. -- 1809-1898 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Hazen, William Babcock, -- 1830-1887 -- Correspondence; Herschel, John F. W. -- 1792-1871 -- Correspondence; Holmes, Oliver Wendell, -- 1809-1894 -- Correspondence; Huxley, Thomas Henry, -- 1825-1895.; Lossing, Benson John, -- 1813-1891 -- Correspondence; Mott, Valentine, -- 1785-1865 -- Correspondence; Newcomb, Simon, -- 1835-1909 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Silliman, Benjamin, -- 1816-1885 -- Correspondence; Smyth, C. Piazzi -- 1819-1900 -- Correspondence; Spencer, Herbert, -- 1820-1903 -- Correspondence; Spofford, Ainsworth Rand, -- 1825-1908 -- Correspondence; Stanton, Edwin McMasters, -- 1814-1869 -- Correspondence; Tyndall, John, -- 1820-1893 -- Correspondence; Welles, Gideon, -- 1802-1878 -- Correspondence; Whitney, J. D. -- 1819-1896 -- Correspondence; Wilberforce, Samuel, -- 1805-1873.; Wood, Thomas John, -- 1823-1906 -- Correspondence; Youmans, William Jay, -- 1838-1901 -- Correspondence; Draper family; Ludlow family; Morey family; American Chemical Society; British Association for the Advancement of Science; New York Meteorological Observatory; New York University. -- Medical Department; Evolution (Biology); Medical colleges -- New York (State) -- New York; Meteorological stations -- New York (State) -- New York; Meteorology -- New York (State) -- New York; Science -- History -- 19th century; Universities and colleges -- New York (State) -- New York; United States -- History -- Civil War, 1861-1865.; Historians; Scientists